The Usage of Financial Derivatives in Financial Risk Management by non- financial Companies in Serbia - Živanović, Branko; Kobilarev, Mina (Industrija, 2017)
In this paper we analyse the research results on corporate risk management practices, notably in light of the derivatives use in the large Serbian non-financial companies. The principal aim of this paper is to examine whether Serbian companies employ derivatives to manage risk and to what degree, and to explore the main rationale behind the companies’ not employing these instruments, as well as to suggest possible enhancements of risk management practices. Furthermore, we have investigated the key reasons why financial derivatives are very useful for Serbian companies for hedging financial risks.  Additionally, this paper provides a comparative overview of the use of derivatives between Serbian companies and the companies in Croatia and Slovenia in order to ascertain whether Serbian companies employ derivatives in order to manage risk to the same degree as their Croatian and Slovenian counterparts.This paper will include findings and provide evidence that FX rate and referent interest rates (such as 1w- 2w repo rate, Beonia and Belibor) are markedly volatile, which opens vast possibilities for the use of financial derivatives, given that these financial parameters determine the price of a credit arrangement for companies and the quality of import and export cash flows.
Keywords: Serbian; Risk management; Risk; Management; Financial derivative; Corporation